EFFECT OF PACLOBUTRAZOL ON THE GROWTH OF POTATO (Solanum tuberosum L.) - Sudarniati Genaly, Tuti; Nurhayati, Nurhayati; Sari Rahayu, Murni (CV. Radja Publika, 2022)
Low potato production in Indonesia is caused by poor seed quality and low availability of potato seeds. One of the efforts to produce superior and quality potato seeds is to apply growth regulators (ZPT) because they can produce a lot of potato seeds, but plant growth becomes depressed. The purpose of this study was to determine the effect of paclobutrazol concentration and application time on the growth of potato G2 (Solanum tuberosum L.). This research was carried outon UPT land. BIH Kutagadung Berastagi, which lasted for four months, from November 2020 to March 2021. The design used in this study was a Factorial Randomized Block Design consisting of 2 factors and repeated 3 times. The first factor is the concentration of the hormone Paclobutrazol (P) which consists of 4 levels, namely: P0 = Control; P1 = 200 ppm; P2 = 400 ppm; P3 = 600 ppm. The second factor was the application time of Paclobutrazol (W) which consisted of 3 levels, namely: W1 = 20 days after planting; W2 = 30 days after planting; W3 = 40 days after planting.The research results show thattreatment of paclobutrazol concentration had no significant effect on the number of leaves and stem diameter, but had a very significant effect on plant height,The time of application of paclobutrazol had no significant effect only on the number of leaves,but have a real effect onplant height, stem diameter,The interaction between concentration and application time of paclobutrazol had no significant effect on leaf number and plant height, but had a very significant effect on stem diameter..